Dynamic Competition with Network Externalities: Why History Matters - Hanna Halaburda; Bruno Jullien; Yaron Yehezkel (Center for Economic Studies and ifo Institute (CESifo), 2016)
We consider dynamic competition among platforms in a market with network externalities. A platform that dominated the market in the previous period becomes “focal” in the current period, in that agents play the equilibrium in which they adopt the focal platform whenever such equilibrium exists. Yet when faced with higher-quality competition, can a low-quality platform remain focal? In the finite-horizon case, the unique equilibrium is efficient for “patient” platforms; with an infinite time horizon, however, there are multiple equilibria where either the low- or high-quality platform dominates. If qualities are stochastic, the platform with a better average quality wins with a higher probability, even when its realized quality is lower, and this probability increases as platforms become more patient. Hence social welfare may decline as platforms become more forward looking.
Keywords: L10; 330; network externalities; dynamic competition; coordination